Characteristics and genesis of carbonate rocks' hydrothermal dissolution in Laiwu Basin, Shandong Province, China. Issue 3 (July 2020) - Yuanqing, Liu; Le, Zhou; Wei, Li; Lin, Lv; Xuemei, Ma; Yidi, Zheng; Shunxiang, Meng; Qijun, Deng
Abstract: Through analysing the chemical composition of rock samples, investigating of hydrogeological points and hydrothermal dissolution geological points, the characteristics and mechanism of hydrothermal dissolution in Laiwu Basin were studied. The results show that the high temperature and high pressure magma intrusions resulted in hydrothermal metamorphic marbling of carbonate rocks in the contact zone. Hydrothermal fluids migrating along permeable faults, fractures can cause acidic hydrothermal dissolution and mixed dissolution in carbonate formation and formed dissolution cavities of different scales. The cavities are constituting groundwater enrichment space at present.